The prevalence of urinary incontinence among the elderly in a rural community in Selangor. - Mohd Sidik, Sherina (Universiti Sains Malaysia, 2010)
Background: Urinary incontinence is a common but poorly understood problem in the elderly population. The aim of this study was to determine the prevalence of urinary incontinence and its associated factors among the elderly in a community setting. Methods: A cross-sectional study design was used. Stratified cluster sampling was used in this study. All elderly residents aged 60 years old and above who fulfilled the selection criteria were included as respondents. The translated Malay version of the Barthel's Index (BI) was used to identify the presence of urinary incontinence. Results: The prevalence of urinary incontinence was 9.9% among the elderly respondents. Urinary incontinence among the elderly was significantly associated with age, gender, depression, functional dependence, and diabetes mellitus (P < 0.05).